Nursing care of a patient undergoing resection of massive brainstem tumor combined with cesarean section at 38 weeks of gestation (1例脑干巨大肿瘤切除手术合并妊娠38周剖宫产手术患者的护理) - LI Yuhua (李玉华); GUO Yanling (郭艳伶); FENG Rui (冯瑞); XING Yunjie (邢云杰); Ma Haihong (马海红); WANG Huazhi (王华枝) (中西医结合护理)
This paper summarized the nursing care of a patient undergoing resection of massive brainstem tumor combined with cesarean section at 38 weeks of gestation. Nursing interventions were carried out including close observation of vital signs, prevention of complications after brainstem tumor resection, prevention of cranial pressure caused by cerebral hernia, improving pulmonary ventilation by prone position, Traditional Chinese and western medicine combined with rehabilitation treatment, enhancement on the separation of maternal and child care after cesarean section and neonatal care, nutrition support and psychological nursing. (本文总结1例脑干巨大肿瘤切除手术合并妊娠38周剖宫产手术患者的护理。医护人员严密观察患者生命体征, 积极预防脑干肿瘤切除术后并发症的发生, 预防颅高压引起的脑疝, 给予俯卧位改善肺部通气, 实施中西医结合康复治疗, 做好母婴分离的剖宫产术后护理和新生儿的护理, 注重营养支持和心理护理。)